Osteoporosis in Menopause & Beyond - Nasreen, SK Zinnat Ara; Shahreen, Safinaz; Parveen, Neaz T (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Abstract not available Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 36-43